Система керування багаторівневим інвертором сонячної електричної станції - Левицький, С.М. (Електротехніка і електромеханіка, 2015)
Розроблено закон керування та структуру мережевого багаторівневого інвертора сонячної електростанції, який дозволяє утримувати режим роботи сонячного модуля в області точки відбору максимальної потужності і збільшити
продуктивність сонячного модуля. Запропоновано вдосконалену модель регулятора поздовжньої складової струму інвертора, яка враховує рівень споживання реактивної потужності з вузла мережі, поточну напругу мережі та напругу
сонячного модуля і дозволяє оптимізувати роботу інвертора як зі сторони сонячного модуля, так і з боку мережі за
напругою. Запропоновано вдосконалену модель регулятора поперечної складової струму інвертора, яка враховує відношення спожитої активної потужності з вузла мережі до поточної потужності сонячного модуля і дозволяє оптимізувати роботу інвертора за навантаженням та частотою. Розглянуто приклад реалізації системи керування інвертором із запропонованими моделями на базі високопродуктивного мікроконтролера. Разработан закон управления и структура сетевого многоуровневого инвертора солнечной электростанции, который
позволяет удерживать режим работы солнечного модуля в области точки отбора максимальной мощности и увеличить производительность солнечного модуля. Предложена усовершенствованная модель регулятора продольной составляющей тока инвертора, которая учитывает уровень потребления реактивной мощности из узла сети, текущее напряжение сети и напряжение солнечного модуля и позволяет оптимизировать работу инвертора как со стороны солнечного модуля, так и со стороны сети по напряжению. Предложена усовершенствованная модель регулятора поперечной составляющей тока инвертора, которая учитывает отношение потребляемой активной мощности из узла сети к текущей мощности солнечного модуля и позволяет оптимизировать работу инвертора по нагрузке и частоте. Рассмотрен пример реализации системы управления инвертором с предложенными моделями на базе
высокопроизводительного микроконтроллера. Purpose. The development of control law for network multilevel
invertor of solar power station and design device for control law
realization. Methodology. At synthesis of control law theory of
automatic control, power network engineering and circuit technique are considered. The control law for distributive control
over the direct-axis and quadrature-axis currents of invertor
after abc-dq transform of three phase current’s momentary
value is used. Results. The improved model of regulator of direct-axis invertor’s current is developed and provides the voltage optimization of invertor’s operating both from solar module
and from network by means of calculation the reactive power
consumption from network, voltage on network and voltage on
solar module. The improved model of regulator of quadratureaxis invertor’s current is developed and provides the power and
frequency optimization of invertor’s operating by means of calculation ratio of active power consumption and power from
solar module. Originality. The offered control law and device,
which realize it, is working out on secondary loop from power
network smart grid with active and reactive power consumption
monitoring. That provides the optimal operation of solar station
both from solar module and from power network. Practical
value. The proposed control law and structure of the network
multilevel invertor for solar power station provide the operate
mode of solar module in maximum power point and increasing
the solar module’s productivity.